Ethan Worker: capstone - Worker, Ethan, artist and filmmaker (Colorado State University. Libraries, 2019)
The artist's statement: When setting out to make new work, my aim is to process and unpack topics and issues that have affected and altered our modern perceptions of reality. By working with significant mental concepts such as memory, self-perception, nostalgia, and escapism, I seek to gain a greater understanding of my own reality, as well as identify the factors and forces that influence many of us in today's landscape. Through digital manipulation and 3d motion-based techniques, I hope to build a sense of reflection and introspection. My aim is to recontextualize these issues of self-realization in the vacuum of a distorted, yet familiar setting. By reframing these topics in a reflective alternative context, distance can be gained from biases and preconceptions, hopefully resulting in a greater ability to step back and contemplate the means by which our individual realities and senses of self are constructed. Working in a digital 3d setting allows for an ability to create this alternate lens of reality, defying physics, social influences, scale, and realism. Instead, symbols of humanity and identity can be reappropriated and viewed within the context of an isolated, singular objectivity. My work doesn't aim to depict the world and all of its complexities photorealistically, but rather it seeks to hold a mirror to these individualized processes within each of our lives; to explore these concepts of mind and worldview in a self-contained, untethered space.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, images of works and videos.
Videos have no spoken word.
Keywords: electronic art